2023
DOI: 10.17269/s41997-023-00777-2
|View full text |Cite
|
Sign up to set email alerts
|

A population-based assessment of avoidable hospitalizations and resource use of non-vaccinated patients with COVID-19

Abstract: Objective The coronavirus disease 2019 (COVID-19) pandemic has precipitated a prolonged public health crisis. Numerous public health protections were widely implemented. The availability of effective and safe vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) presented an opportunity to resolve this crisis; however, vaccine uptake was slow and inconsistent. This study evaluated the potential for preventable hospitalizations and avoidable resource use among eligible non-vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Vaccination is effective to reduce severe cases of SARS-CoV-2 infections requiring ICU admission or MV (13,22,23). A recent retrospective population-based cohort study of 1,053 patients admitted to the ICU showed that the cumulative frequency of ICU admissions for unvaccinated, partially vaccinated, and fully vaccinated patients was 230.6, 30.8, and 5.5/100,000 population, with potential for 1,028 avoidable ICU admissions and total avoidable costs of $61.3 million CAD in one Canadian province (24). However, our study focuses on the unfortunate subset that developed critical illness from COVID-19, and who are often neglected in population-based studies in which ICU admission is often an outcome rather than a study population.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is effective to reduce severe cases of SARS-CoV-2 infections requiring ICU admission or MV (13,22,23). A recent retrospective population-based cohort study of 1,053 patients admitted to the ICU showed that the cumulative frequency of ICU admissions for unvaccinated, partially vaccinated, and fully vaccinated patients was 230.6, 30.8, and 5.5/100,000 population, with potential for 1,028 avoidable ICU admissions and total avoidable costs of $61.3 million CAD in one Canadian province (24). However, our study focuses on the unfortunate subset that developed critical illness from COVID-19, and who are often neglected in population-based studies in which ICU admission is often an outcome rather than a study population.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of vaccines have been developed to prevent SARS-CoV-2 infection and subsequent COVID-19 disease [ 12 ]. Numerous studies found, as a result of vaccine administration, a lower incidence of hospitalization for COVID-19 pneumonia, fewer hospitalized patients with respiratory distress and requiring supplemental oxygen, as well as reduced need for ICU admission [ 53 , 54 , 55 ]. In particular, a recent comparative analysis of clinical outcomes conducted in Spain on 232 adult patients hospitalized with COVID-19 showed that a complete vaccination schedule of either mRNA or adenovirus vaccines protected patients from progression to severe disease or death compared to unvaccinated patients [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nor did we assess some potential confounding factors, such as previous SARS-CoV-2 infection or time between the data of vaccination and the onset of disease. Moreover, it would have been interesting to consider the effects of the restrictive measures, the risk management, and the communication plans implemented by the government during the pandemic [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%